A review of building integrated photovoltaic: case study of tropical climatic regions - Mu’azu Mohammed Abdullahi; Abdullahi Abubakar Mas’ud; Ibrahim Abubakar Mas’ud; Jorge Alfredo Ardila-Rey; Firdaus Muhammad-Sukki; Ridoan Karim; Ahmad Shakir Mohd Saudi; Nurul Aini Bani; Asan Vernyuy Wirba (Institute of Advanced Engineering and Science, 2021)
The building integrated photovoltaic (BIPV) system have recently drawn interest and have demonstrated high potential to assist building owners supply both thermal and electrical loads. In this paper, the BIPV technology has been reviewed, in terms of its performance, efficiency and power generation capacity. Specifically, the applications of the BIPV in tropical climate regions have been discussed, together with its prospects and challenges. For these schemes to be implemented in a tropical climatic region, the following issues must be considered: 1) Certain studies must be done relating to electrical load demand, predicted PV output, location of the buildings and its integration and constraints associated with roof design; 2) For the highest energy production from solar PV, the solar collectors need to be with the right tilt depending on the location; 3) Design criteria such as safety, efficiency, durability, flexibility and constructive issues need to be considered; 4) The government of such countries must train electricians and carpenters on PV installations; 5) The BIPV roofing must perform same function as normal roofing materials, such as noise protection, water tightness, insulation and climate protection, and 6) As practiced around the world, these countries must establish design standards for the BIPV.